Trinidad Cocoa - Drying The Beans - (:unkn) unknown (The Imperial Institute, 2009)
Shows workers on a shed rubbing cocoa beans beans to allow air to flow evenly through the beans and to aid with the drying. In the background is the large plantation house.
Colour; Black and White; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cocoa trade; Agriculture; Dwellings